Role of the mechanical microenvironment in cancer development and progression - Liu, Qiuping; Luo, Qing; Ju, Yang; Song, Guanbin (Cancer biology & medicine, 2020)
Cross-talk between tumor cells and mechanical stress in the tumor microenvironment has been shown to be involved in carcinogenesis. High mechanical stress in tumors can alter the metabolism and behaviors of cancer cells and cause cancer cells to attain cancer stem-like cell properties, thus driving tumor progression and promoting metastasis. The mechanical signal is converted into a biochemical signal that activates tumorigenic signaling pathways through mechanotransduction. Herein, we describe the physical changes occurring during reprogramming of cancer cell metabolism, which regulate cancer stem cell functions and promote tumor progression and aggression. Furthermore, we highlight emerging therapeutic strategies targeting mechanotransduction signaling pathways.